Laboratory test trends within 72 hours of hospital admission associated with death among COVID-19 patients. Issue 50 (16th December 2022) - Zambrano, Sarah; Davis, Megan; Leeds, David R.; Noronha, Kelvin; McLaughlin, Angela; Burns, Rebecca H.; Mulvey, Elizabeth; Linas, Benjamin P.; Assoumou, Sabrina A.
Abstract : Early identification of patients at risk for severe coronavirus disease 2019 (COVID-19) is crucial for appropriate triage and determination of need for closer monitoring. Few studies have examined laboratory trends in COVID-19 infection and sought to quantify the degree to which laboratory values affect mortality. We conducted a retrospective cohort (n = 407) study of hospitalized patients with COVID-19 early in the course of the pandemic, from March 16th to April 8th, 2020 and compared baseline to repeat laboratory testing 72 hours into admission. The primary outcome was death. We found that rises of 25 mg/L C-reactive protein, 50 units/L lactate dehydrogenase, and 100 ng/mL ferritin were associated with 23%, 28%, and 1% increased odds of death, respectively. In contrast, changes in fibrinogen, D-dimer, white blood cell count, and creatinine in the first few days of hospital admission were not associated with mortality. These quantitative findings may assist clinicians in determining the risk of potential clinical decline in patients with COVID-19 and influence early management.